Making a mark: Transforming everyday work of city arborists into dance - Ingram, Matthew Bruce; Wallace, Ian Mitchell (Frontiers in Communication, 2022)
This article expands on previous scholarship on the choreographic practice of marking by studying two disparate communities—community-based dance makers and arborists—who collaborate to create a large-scale, public dance performance. With the dance company's goal being to bring public awareness to the embodied skillfulness of the city's urban forestry department and the impacts these city workers have on the community green spaces they service, the dancers for the performance are the foresters themselves who enact dancerly versions of their professional movements. We analyzed 21 hours of videotaped data of dance rehearsals, proffering up an interaction-based approach to the study of marking, analyzing the moment-to-moment way, both groups mark out dance phrases for a sub-section of the final performance: the brush truck routine. In doing so, we develop the term marking together to denote how dance ideas are built, transformed, and enacted through group idea formation and revision. Ultimately, we provide insights into how to study dance marking in its full, interactional complexity.